Mulheres e educação: um estudo sobre o grupo de mulheres brasileiras (GMB) do Bairro do Benguí - Belém - Pará - CONCEIÇÃO, Heloisa Helena Meireles Bahia (Universidade Federal do Pará, 2012)
The paper presents the research conducted in the period 2009-2010, which aimed to study the Brazilian Women's Group (GMB), seeking to verify the performance of an executor of educational practices in addition to the institutional procedures. The overall objective was to investigate how research have been ongoing educational practices geared to the lines of action (women's health, combating violence, work and income) developed by the group, the specific objectives were to identify the factors that led women in the group to choose three courses of action to be developed; whether there has been positive or negative consequences in the neighborhood of Bengü after creating it, to know the reasons why women of the neighborhood group to integrate, analyze the educational process that involves practices of the group. Our research problem is based on the following question: In what ways are the educational practices of the health activities of women, combating violence, employment and income in developed GMB? The methodology used was predominantly qualitative approach. We conducted a field survey and documentary. We use non-participant observations and application of semi-structured interviews with a pre-established. We use a strategy called study. The time frame of the research was the period of 2008-2010, which includes the mandate of the current coordinator of the group, with completion scheduled for September 2011. The analysis revealed that the educational practices aimed at three lines of action are being developed through lectures, campaigns, public events, seminars, meetings, distribution of textbooks, courses and training workshops, counseling women victims of violence, etc.. The opinions of the interviewees were unanimous with regard "to the educational nature of the actions developed by the group." They claim that the activities aimed at training subjects, training for the labor market, enabling people to understand their rights and duties in society, workshops and courses to help generate jobs and income, etc.. The lack of financial resources is an issue also mentioned by all interviewees, as reported in need of financial support to carry out the actions, the group raises funds through the development of projects that are sent to various institutions, and that when a project is approved, the money is spent on offering courses, workshops, campaigns, among others. It should be noted that in addition to positive action in the fight against prejudice imposed on women, the GMB acts to compensate the development of policies that the state does not hold account. Thus, the educational process is embodied in everyday courses and workshops, but primarily in the development of everyday cultural practices, social and political.